ANALISIS RENDAHNYA MOTIVASI BELAJAR SISWA DAN PENANANGANANNYA (STUDI KASUS) - Samsaifil Samsaifil; Iman Hidayat (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
This research aims to determine the causes of low learning motivation problems of AD students and solutions to overcome them at SMPN 4 East Kabaena. The main problem in this research is the low learning motivation of students with the initials AD at SMP Negeri 4 East Kabaena. The method used is a case study with a descriptive qualitative approach. The subject in this research was 1 student with the initials AD who experienced low learning motivation. Data collection techniques used interviews, observation and documentation. Data analysis techniques in this research used data reduction and for data validity used triangulation. The results of the research showed that the cause of AD students experiencing low learning motivation was because AD felt ignored and did not receive good attention from his parents, then handled using individual counseling, after being handled AD began to understand himself and promised to improve himself. Through this change shows that individual counseling services can alleviate the problem of low student learning motivation.